Pola Permukiman Pesisir Desa Nelayan Muncar (Studi Kasus: Dusun Sampangan, Banyuwangi) - Cayarini, Filomina Dwi (Universitas Medan Area, 2025)
Sampangan Hamlet is part of Muncar Fishing Village, which is experiencing regional development that affects the physical condition of the environment. The changing physical condition of the environment can certainly affect the shape or settlement pattern of this fishing village. This study aims to reveal the coastal settlement pattern of Muncar Fishermen Village, where it is located in Sampangan Hamlet, Banyuwangi. The research method used is qualitative, using spatial analysis with GIS, and supporting data from documents, interviews, and field observations. The results of the study show that in the aspect of seaside settlement patterns in the form of perpendicular parallel to the sea line, while those located some distance away have a mixed pattern (grid and spinal), the use of open space there are 2 types, namely diffuse and centralized patterns, the location and orientation of settlements in the form of land space and transitions, a circulation hierarchy consisting of collective, local, and environmental, and 44.86% land use for settlements.